PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN MODEL JIGSAW PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS V SD NEGERI 07 LIBO JAYA KABUPATEN SIAK - Miranda Novita Permata Sari Lubis; Adrias; Yesni Yenti; Nur Azmi Alwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students' speaking skills in Indonesian Language learning through the application of the Jigsaw cooperative learning model in class V of SD Negeri 07 Libo Jaya, Siak Regency. The background of this study was the low speaking skill of students, shown by only 26% of students reaching the minimum mastery criteria before the action was carried out. This research used a Classroom Action Research (CAR) design following the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection, carried out in two cycles. The subjects were 31 fifth-grade students and the classroom teacher as observer. Data were collected through performance tests and observation sheets covering the aspects of pronunciation, diction, intonation, fluency, and comprehension, then analyzed descriptively using averages and percentages of mastery. The results showed a consistent improvement across cycles: the lesson plan (RPPM) score increased from 82.1% in Cycle I Meeting 1 to 92.8% in Cycle II; teacher performance increased from 82.5% to 95%; and student performance increased from 85% to 92.5%. The average speaking-skill score rose from 73 in Cycle I Meeting 1 to 84.83 in Cycle II, with 87.10% of students reaching the mastery criterion. The most notable gains occurred in the fluency and intonation aspects. It is concluded that the Jigsaw model effectively improves elementary students' speaking skills in Indonesian Language learning.